Ameloblastic fibro-odontoma associated with paresthesia of the chin and lower lip in a 12-year-old girl. (August 2019) - Saeed, Dereen Mohammed; Setty, Suman; Markiewicz, Michael R; Cabay, Robert J
Ameloblastic fibro-odontoma is a rare, benign, and slowly growing neoplasm of the jaw composed of proliferating odontogenic epithelium in ectomesenchymal tissue along with dental hard tissue formation. Herein, we describe a case of an ameloblastic fibro-odontoma in 12-year-old female with paresthesia of the chin and lower lip. Panoramic radiography showed a radio-opacity in the right posterior mandible near the mandibular canal and associated with the right mandibular third molar. Histologically, the lesion contained epithelial and mesenchymal odontogenic components in close proximity to odontoma-like elements. Enucleation and curettage of the affected site in the mandible resulted in resolution of the paresthesia postoperatively.